2003
DOI: 10.1063/1.1628834
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of polycrystalline ZnO thin-film transistors

Abstract: Thin film transistors (TFTs) made of transparent channel semiconductors such as ZnO are of great technological importance, because their insensitivity to visible light makes device structures simple. In fact, several demonstrations are made on ZnO TFT achieving reasonably good field effect mobilities of 1-10 cm2/Vs, but reveal insufficient device performances probably due to the presence of dense grain boundaries. We have modeled grain boundaries in ZnO thin film transistors (TFTs) and performed device simulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
200
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(211 citation statements)
references
References 36 publications
11
200
0
Order By: Relevance
“…It was reported that traps in the dense grain boundaries of crystalline ZnO can severely affect the overall performance of the TFTs. 8 In addition, the control of grain nucleation and uniformity of grain size at the critical gate insulator-semiconductor interface make crystalline ZnO a challenging and unfavorable choice for use in the economical bottom gate TFT structure used in current large-area display. More recently, amorphous indium-gallium-zinc oxide ͑IGZO͒ has been studied and developed, revealing a new path for producing high mobility amorphous semiconductor material through multicomponent post-transition-metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that traps in the dense grain boundaries of crystalline ZnO can severely affect the overall performance of the TFTs. 8 In addition, the control of grain nucleation and uniformity of grain size at the critical gate insulator-semiconductor interface make crystalline ZnO a challenging and unfavorable choice for use in the economical bottom gate TFT structure used in current large-area display. More recently, amorphous indium-gallium-zinc oxide ͑IGZO͒ has been studied and developed, revealing a new path for producing high mobility amorphous semiconductor material through multicomponent post-transition-metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…When the gate bias is higher than the threshold voltage, band bending at the interface allows the formation of a conductive channel. Potential barriers at grain boundaries are also lowered by the gate potential [27][28][29][30] and the current flow proceeds perpendicular to nanocolumns toward the drain contact.…”
Section: Transistor Fabricationmentioning
confidence: 99%
“…The total density of states g(E) is assumed to have exponential distribution of donor (D) like and acceptor (A) like defects that follow the equations 4a and 4c, respectively. This DOS model is attractive because of its simplicity and accuracy and has been used as the basis for many studies on metal oxide based TFTs (Hossain et al, 2003(Hossain et al, , 2004Fung et al, 2009;Ming et al, 2009) . Additionally, traps at the semiconductor -dielectric interface are assumed, which are defined by their concentration (N it ) and energy level (E it ).…”
Section: Importance Of Simulation Studies In Analysis Of Thin Film Trmentioning
confidence: 99%
“…In traditional electronics, device modelling and simulation has proven to be of great help in not only understanding the detailed device operation but has also served as a powerful tool to design and improve devices. The physics based device simulation is also becoming beneficial to the research area of organic and metal oxide semiconductors TFTs, where it is effectively predicting the device behaviour, giving insight into the underlying microscopic mechanisms and providing intuitive information about the performance of a new material (Bolognesi, 2002;Gupta et al, , 2009Gupta et al, , 2010Hill, 2007;Hossain, 2003;Scheinert, 2004). Its continued involvement for explaining various device phenomenons will certainly be of great use for future developments.…”
Section: Introductionmentioning
confidence: 99%